Metabolomics for undergraduates: Identification and pathway assignment of mitochondrial metabolites. Issue 1 (5th November 2015) - Marques, Ana Patrícia; Serralheiro, Maria Luisa; Ferreira, António E.N.; Freire, Ana Ponces; Cordeiro, Carlos; Silva, Marta Sousa
Abstract: Metabolomics is a key discipline in systems biology, together with genomics, transcriptomics, and proteomics. In this omics cascade, the metabolome represents the biochemical products that arise from cellular processes and is often regarded as the final response of a biological system to environmental or genetic changes. The overall screening approach to identify all the metabolites in a given biological system is called metabolic fingerprinting . Using high‐resolution and high‐mass accuracy mass spectrometry, large metabolome coverage, sensitivity, and specificity can be attained. Although the theoretical concepts of this methodology are usually provided in life‐science programs, hands‐on laboratory experiments are not usually accessible to undergraduate students. Even if the instruments are available, there are not simple laboratory protocols created specifically for teaching metabolomics. We designed a straightforward hands‐on laboratory experiment to introduce students to this methodology, relating it to biochemical knowledge through metabolic pathway mapping of the identified metabolites. This study focuses on mitochondrial metabolomics since mitochondria have a well‐known, medium‐sized cellular sub‐metabolome. These features facilitate both data processing and pathway mapping. In this experiment, students isolate mitochondria from potatoes, extract the metabolites, and analyze them by high‐resolution mass spectrometry (using an FT‐ICR mass spectrometer). The resulting mass list is submitted to an online program for metabolite identification, and compounds associated with mitochondrial pathways can be highlighted in a metabolic network map. © 2015 by The International Union of Biochemistry and Molecular Biology, 44:38–54, 2016.